Notes on the Tardigrada of Thailand, with a description of Macrobiotus alekseevi sp. nov. (Eutardigrada, Macrobiotidae) - Tumanov, Denis V. (Zootaxa, 2005)
Ten tardigrada species were extracted from samples, collected in Thailand. One of them Macrobiotus alekseevi is new for science. It belongs to the richtersi-group of the genus Macrobiotus. The new species differs from all known species of this group mainly by the characters of the egg processes.